(3EVGAI GdQGehS hEVGaI GdfGehS Ydi EVGAI GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3aUd GdMGA GdegedI (B( (3ef HGH GdHGA(B) (3, bhdg (B: (3GdLhGH cchcH EdN bdJ (B: (3CTGQ HhRfg Edi RjGOI GdhGh hgh GdCUM hbjd GdhGh CUdjI hGdgeRI gi GdRGFOI , hYdjg ajPcQ ai M h H s
(3BNQgG (B:s
(3ef aUd GdjGA(B( (3ef HGH GdLje (B) (3, bhdg (B: (3bdJ (B: (3hcCfg de jYQH GfJgi HGH GdLje HMeO Gddg , hjdjg HGH GdMGA GdegedI , hGddg Gdehab ddUhGH s
(3deNWhW ajI VHW CMjGfGs
(3Hg fXGe GdJYbjHIs
(3cJHJ YfhGfGJgG HGdeOGO GdCRQb hGdCMeQs
(3fSNI KGdKI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
Keywords: (3GddZIs